Infeasible Mehrotra-type predictor–corrector algorithm for cartesian P*(κ) nonlinear complementarity problems over symmetric cones. Issue 3 (4th March 2019) - Zhao, Huali; Liu, Hongwei
ABSTRACT: This paper establishes a theoretical framework of infeasible Mehrotra-type predictor–corrector algorithm for CartesianP ∗ ( κ ) nonlinear complementarity problems over symmetric cones which can be regarded as an extension of Liu et al. [ Polynomial convergence of Mehrotra-type predictor–corrector algorithm for the CartesianP ∗ ( κ ) -LCP over symmetric cones, Optimization 64(4) (2013), pp. 1–23] for CartesianP ∗ ( κ ) linear complementarity problems over symmetric cones to CartesianP ∗ ( κ ) nonlinear complementarity problems over symmetric cones. The iteration complexities of the proposed algorithm are estimated and some numerical results are provided. The numerical results show that the proposed algorithm is efficient and reliable.